This poison heart - Bayron, Kalynn (New York : Bloomsbury, 2021)
Teenaged Briseis, who possesses a supernatural power over plants, even poisonous ones, inherits a dilapidated estate in rural New York and must protect herself and her family from centuries-old secrets that threaten their lives.
Junior Library Guild
Ages 14-17.
Grades 9-12.
A Junior Library Guild selection
Keywords: Ability -- Juvenile fiction; African Americans -- Juvenile fiction; Plants -- Juvenile fiction; Supernatural -- Juvenile fiction; Ability -- Fiction; African Americans -- Fiction; Plants -- Fiction; Supernatural -- Fiction; Ability -- Fiction; African Americans -- Fiction; Plants -- Fiction; Supernatural -- Fiction